2013
DOI: 10.1371/journal.pone.0077614
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variants of Staphylococci and Their Underlying Population Distributions Following Exposure to Stress

Abstract: This study investigated whether alterations in environmental conditions would induce the formation of small colony variant phenotypes (SCV) with associated changes in cell morphology and ultra-structure in S. aureus, s. epidermidis, and S. lugdunensis. Wild-type clinical isolates were exposed to low temperature (4°C), antibiotic stress (penicillin G and vancomycin; 0-10,000 µg mL-1), pH stress (pH 3-9) and osmotic challenge (NaCl concentrations of 0-20%). Changes in cell diameter, cell-wall thickness, and popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
78
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 37 publications
9
78
0
1
Order By: Relevance
“…The changes observed in the metabolome and proteome may represent a phenotypic shift that can occur within an existing population of cells without cell division. Such a shift may be indicative, for example, of the formation of small colony variants that have been previously shown to form in response exposures to NaCl, with accompanying reduced metabolism compared to wild‐type bacteria (Crompton et al, ; Onyango et al, ; Proctor et al, ; von Eiff, ). Prior investigations have shown that small colony variants have slower growth rates, reduced production of virulence factors and some are auxotrophic for important compounds such as haemin and menadione (Bui et al, ; Moisan et al, ; Proctor et al, ; von Eiff et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes observed in the metabolome and proteome may represent a phenotypic shift that can occur within an existing population of cells without cell division. Such a shift may be indicative, for example, of the formation of small colony variants that have been previously shown to form in response exposures to NaCl, with accompanying reduced metabolism compared to wild‐type bacteria (Crompton et al, ; Onyango et al, ; Proctor et al, ; von Eiff, ). Prior investigations have shown that small colony variants have slower growth rates, reduced production of virulence factors and some are auxotrophic for important compounds such as haemin and menadione (Bui et al, ; Moisan et al, ; Proctor et al, ; von Eiff et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamic acid can readily be used for energy production by oxidation and it is required for the synthesis of the peptidoglycan bacterial cell wall, especially relevant if cell wall thickening is part of the response to a NaCl challenge (Doublet, Heijenoort, & Mengin‐Lecreulx, ). It has been shown that in staphylococcal species, the thickness of the cell wall was significantly altered following exposures to environmental changes including elevated NaCl (Onyango et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased cell sizes indicated disruption of cell divisions and slower growth rate in the treated cells [2527]. Although the cell multiplication was abruptly slowed or stopped, the cellular metabolic processes remained unaffected, hence the increased cell size; that leads to the release of autolytic enzyme under lethal concentrations of inhibitory agents, which in the end resulted in the destruction and deterioration of the treated cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of staphylococci to grow over a wide range of environmental conditions has been demonstrated (Prescott, Harley, & Klein, 2002), and related to their capability to rapidly adapt to harsh conditions, surviving and taking advantage when optimal or less limiting conditions are restored (Onyango, Hugh Dunstan, Roberts, Macdonald, & Gottfries, 2013). This adaptation process is clearly revealed during plate counting by the presence of colonies showing morphological differences, including variation in colony size, pigmentation and haemolytic irregularities (Kipp, Becker, Peters, & von Eiff, 2004;Onyango, Hugh Dunstan, Gottfries, Von Eiff, & Roberts, 2012).…”
Section: Discussionmentioning
confidence: 99%